Charakterystyka międzynarodowych porozumień licencyjnych z punktu widzenia potrzeb analizy ekonomicznej - Kulpa, Franciszek (Wydział Prawa i Administracji UAM, 1977)
This paper deals with economic contents of international licence agreements. The article consists of two parts. In the first part the author presents an essence and an object of international licence contracts. He shows that the licences are the specific agreements which have not the parallels in a traditional form of a commodity turnover or of a capital movement. In the second part of this article they are presented transactions integrally connected with the licence. It was there also exhibited the licence as a component of economic undertakings as follows: contracts for buy and sale of complete industrial equipment, contracts for industrial cooperation and contracts for joint ventures.
The Characteristics of the International Licence Agreements from Economic Analysis Point of View